ASP Strategies and Appropriate Antibiotic Use. (4th October 2017) - Lee, Brian R; Tribble, Alison; Handy, Lori; Gerber, Jeffrey S; Hersh, Adam L; Kronman, Matthew; Terrill, Cindy; Newland, Jason
Abstract: Background: The Infectious Diseases Society of America (IDSA) recommends hospitals implement antimicrobial stewardship programs (ASP) in order to decrease inappropriate antibiotic use due to the rise in antibiotic-resistant infections. Data are limited on the extent to which different ASP strategies influence appropriate antibiotic use. Methods: We conducted an online survey in 2016 of U.S. Children's Hospitals to collect hospital-level information on dedicated ASP effort, ASP monitoring activities, use of audit-feedback, formulary restrictions, rapid diagnostics, etc. During the same period the ASP teams at these hospitals completed 3 point prevalence surveys that documented details on all admitted patients 0–17 years receiving any antibiotics, determined what ASP modifications could be made, and if the antibiotic was appropriate. We employed hierarchical, multivariable logit models to examine which ASP-related, hospital-level strategies were associated with appropriate antibiotic use. Results: Thirty hospitals participated. A total of 6, 921 patients were included, representing 10, 068 total antibiotics. Of these orders, 8, 554 (85.0%) were categorized as appropriate, though this varied across sites (range: 68-92%). Additionally, 78.2% of antibiotics did not have recommended modifications. Appropriate antibiotic use was significantly higher for hospitals that relied on rapid diagnostics (aOR: 1.6; P < 0.001) or monitored their days of therapy (DOT) rate (aOR: 1.4; P < 0.001), whereas the presence of either audit-feedback (aOR: 1.04; P = 0.75) or formulary restrictions (aOR: 0.83; P = 0.059) were not associated. Having annual education for all prescribers had increased likelihood of antibiotics having no modification recommendations (aOR: 1.45; P = 0.037). Total ASP FTE was not correlated with hospital-level percent appropriate use (corr: −0.05; P = 0.79) or antibiotic modification recommendations (corr: −0.08; P = 0.67). Conclusion: Routine monitoring of DOT rates and utilization of rapid diagnostics were associated with appropriate antibiotic use. Additional analysis is needed to understand additional factors that can aid hospitals in developing and maintaining ASPs to reduce inappropriate antibiotic use. Disclosures: B. R. Lee, Merck: Grant Investigator, Grant recipient. PCORI: Grant Investigator, Grant recipient. C. Terrill, Merck: Grant Investigator, Research grant Allergan: Grant Investigator, Research grant. J. Newland, Merck: Grant Investigator, Research grant. Allergan: Grant Investigator, Research grant